The predictive value of self-reported allergies for reoperation after index hip arthroscopy. Issue 1 (4th February 2022) - Srikumar, Syian; Feingold, Jacob D; Swartwout, Erica L; Roberts, Sacha A; Ranawat, Anil S
ABSTRACT: The purpose of this study is to compare the rate of reoperation after index hip arthroscopy for symptomatic femoroacetabular impingement in patients with, and without, at least one self-reported allergy. Data were collected prospectively in 1468 patients whose records were retrospectively reviewed. After the application of inclusion and exclusion criteria, two cohorts were formed: (i) a study cohort ( n  = 261) composed of patients with a self-reported allergy and (ii) a control cohort. ( n  = 666). The allergy cohort had a significantly larger [ P  < 0.001] reoperation rate (24.1% [63/261]) compared to the control cohort (9.6% [64/66]). Univariate analysis (UVA) and multivariate analysis (MVA) were then performed to better understand the implications of allergy status on the arthroscopic outcome. On UVA the presence of an allergy increased the odds of reoperation after index hip arthroscopy by 2.99 [OR (95% CI): 2.99 (2.04, 4.39); P  < 0.001] and for each additional allergy a patient reported, their odds of subsequent surgery increased by 1.27 per allergy [OR (95% CI): 1.27 (1.15, 1.39); P  < 0.001]. However, on the MVA, allergy status was not an independent risk factor for reoperation. These findings suggest that allergy status is associated with a higher reoperation rate, however, allergy status alone cannot prognosticate the risk of subsequent surgery. Therefore, allergy status and its association with future surgery after hip arthroscopy should be considered in the context of multiple patient-specific factors that influence the surgical outcome. An understanding of this association enables patient-centered care and will strengthen the physician–patient relationship.